A microporous membrane and its preparation method and application
By using a microporous membrane loaded with platinum group metal nanooxides and composited with a polytetrafluoroethylene fiber membrane in the proton exchange membrane, the problem of poor infiltration performance of ePTFE microporous membrane is solved, and the conductivity and durability of the proton exchange membrane are improved. , achieving higher fuel cell performance.
Patent Information
- Application Number
- CN202210600922.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-30
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2042-05-30
AI Technical Summary
The existing proton exchange membranes have attenuated performance under high temperature conditions, and the infiltration performance and hydrophilicity of the ePTFE microporous membranes have poor results in low conductivity and poor durability, which is difficult to meet the strict requirements of fuel cells for membrane materials.
The microporous membrane loaded with platinum group metal nanooxides is combined with the polytetrafluoroethylene fiber membrane to improve the infiltration performance and self-humidification performance, and enhance the anti-electrochemical degradation performance through the free radical quenching of the platinum group metal.
It significantly improves the conductivity and durability of the proton exchange membrane, reduces the hydrogen transmittance, extends the membrane life, and improves the overall application performance.
Smart Images

Figure CN114899464B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of proton exchange membranes, and in particular relates to a microporous membrane and a preparation method and application thereof. Background Art
[0002] Environmental pollution and energy problems are becoming more and more prominent. Hydrogen-oxygen fuel cells and PEM water electrolysis hydrogen production are considered to be one of the important methods to solve environmental pollution and energy problems. Proton exchange membrane is an important component in fuel cells and PEM water electrolysis hydrogen production technology. Fuel cells have very high requirements for proton exchange membranes. Proton exchange membranes are responsible for conducting protons and blocking reaction gases, such as high proton conduction capacity, low reaction gas permeability, certain mechanical strength, good chemical and electrochemical stability, etc., and have become a research hotspot for hydrogen energy technology and membrane technology.
[0003] Although Dupont's traditional Nafion membrane exhibits excellent electrochemical and mechanical properties at low temperatures, the amount of perfluorosulfonic acid resin used is large, the film is relatively thick, and the price is expensive, and performance decay occurs under high temperature conditions. Especially when the battery operating temperature reaches a high temperature of more than 80°C, the conductivity of the proton exchange membrane and the battery output performance are affected by the environment and decay to a certain extent. The main reason for this phenomenon may be that as the temperature rises, the water in the proton exchange membrane evaporates, the Nafion gradually dehydrates, and the structure of the hydrophilic phase in the membrane is damaged to a certain extent, which directly affects the proton transport in the membrane, resulting in a decrease in the proton conductivity of the membrane. In addition, since the glass transition temperature of the traditional Nafion series perfluorosulfonic acid proton exchange membrane is low, the structural damage at high temperature limits its application under high temperature conditions. With the development of hydrogen energy technology, the improvement of the quality of perfluorosulfonic acid resin and membrane making process, the proton exchange membrane is also being optimized and developed. Since Penner RM, Matrin CR (Ion-transporting Composite Membrane, Nafion-impregnated Gore-tex) first immersed Nafion solution into expanded polytetrafluoroethylene (ePTFE, ePTFE is used to refer to expanded polytetrafluoroethylene) microporous membrane material to prepare and apply composite proton exchange membrane, the application of ePTFE microporous membrane has greatly improved the performance of composite proton exchange membrane. The ePTFE microporous membrane itself has good mechanical properties and hydrophobicity, which can well maintain the size of the proton exchange membrane, greatly reduce the swelling deformation of the proton exchange membrane, reduce the thickness and resistance of the proton exchange membrane, and greatly improve the durability and practical performance of the fuel cell proton exchange membrane. However, due to the deviation of the wettability of the ePTFE microporous membrane, it is not conducive to the infiltration of the perfluorosulfonic acid resin solution, resulting in a small amount of perfluorosulfonic acid resin entering the ePTFE micropores, so that the conductivity of the proton exchange membrane is difficult to improve and the durability is poor. In addition, due to the deviation of the wettability of the ePTFE microporous membrane and the strict requirements of the fuel cell on the membrane material, higher requirements are placed on the porosity, mechanical properties and wettability composite processing performance of the expanded polytetrafluoroethylene membrane material.
[0004] At present, a large number of studies on the resistance of proton exchange membranes to electrochemical degradation are to directly add antioxidants to homogeneous membranes, and some are to add antioxidants to Nafion solutions to prepare composite proton exchange membranes with ePTFE microporous membranes. For the above two modification methods, it is still difficult to change the wetting properties of perfluorosulfonic acid resin solutions, and it is difficult to achieve uniform dispersion of antioxidants.
[0005] Therefore, it is necessary to solve the problem of poor hydrophilicity and wettability of ePTFE microporous membrane in the process of preparing composite enhanced proton exchange membrane. Summary of the invention
[0006] In view of this, an object of the present invention is to provide a microporous membrane, wherein the nano-oxide loaded with platinum group metals is a hard chemically inert material having the advantages of small particle size, large specific surface area, good hydrophilicity, strong surface adsorption, high surface energy, good mechanical properties, high wear resistance, dimensional stability, etc., and is a good carrier reinforcement material. When the nano-oxide loaded with platinum group metals is composited with a polytetrafluoroethylene fiber membrane, the wetting performance and self-humidifying performance of the microporous membrane can be improved; at the same time, the platinum group metal loaded with the nano-oxide of platinum group metals is a good free radical quencher, which can quench free radicals in the use of the composite proton exchange membrane, is beneficial to the attachment of perfluorosulfonic acid resin and resistance to electrochemical degradation, reduces the hydrogen permeability of the proton exchange membrane, and improves the life of the entire proton exchange membrane.
[0007] Another object of the present invention is to provide a method for preparing a microporous membrane.
[0008] Another object of the present invention is to provide a proton exchange membrane.
[0009] Another object of the present invention is to provide a method for preparing a proton exchange membrane.
[0010] To achieve the above objectives, the first embodiment of the present invention provides a microporous membrane, comprising a polytetrafluoroethylene fiber membrane body and nano-oxide particles loaded with platinum group metals; the nano-oxide particles loaded with platinum group metals are uniformly distributed in the pores of the polytetrafluoroethylene fiber membrane body.
[0011] The microporous membrane of the embodiment of the present invention, the nano-oxide loaded with platinum group metals is a hard chemically inert material, has the advantages of small particle size, large specific surface area, good hydrophilicity, strong surface adsorption, high surface energy, good mechanical properties, high wear resistance, dimensional stability, etc., is a good carrier reinforcement material, and it is compounded with a polytetrafluoroethylene fiber membrane to improve the wetting performance and self-humidifying performance of the microporous membrane; at the same time, the platinum group metal loaded with the nano-oxide of the platinum group metal is a good free radical quencher, which can quench free radicals in the use of the composite proton exchange membrane, is beneficial to the attachment of perfluorosulfonic acid resin and resistance to electrochemical degradation, reduces the hydrogen permeability of the proton exchange membrane, and improves the life of the entire proton exchange membrane.
[0012] In some embodiments of the present invention, the diameter of the polytetrafluoroethylene fiber is 50-500 nm, and the average pore size is 100-400 nm; the particle size of the nano-oxide particles loaded with platinum group metals is below 100 nm.
[0013] In some embodiments of the present invention, the nano-oxide particles loaded with platinum group metals are hydrophilic particles; the nano-oxide is one or more of nano-silicon dioxide, nano-titanium dioxide, and nano-zirconium dioxide.
[0014] In some embodiments of the present invention, the loading amount of platinum group metal in the nano-oxide particles loaded with platinum group metal is 1-50wt%; the mass ratio of the polytetrafluoroethylene fiber membrane body to the nano-oxide particles loaded with platinum group metal is 100:1-20.
[0015] To achieve the above object, the second embodiment of the present invention provides a method for preparing a microporous membrane, comprising:
[0016] The precursor solution of the platinum group metal is mixed with the nano-oxide powder for reaction, and then centrifugally separated and calcined to obtain the nano-oxide particles loaded with the platinum group metal;
[0017] The polytetrafluoroethylene resin powder and the nano-oxide particles loaded with platinum group metals are mixed and matured, and extruded under the action of a lubricant to form a raw material blank;
[0018] The raw material blank is rolled to form a first rolled film, and the first rolled film is dried to obtain a second rolled film;
[0019] The microporous membrane can be obtained by sequentially stretching the second calendered membrane longitudinally and transversely and then sintering and shaping.
[0020] The beneficial effects of the method for preparing the microporous membrane of the embodiment of the present invention are: improving the hydrophilicity and wettability of the microporous membrane; improving the chemical degradation resistance of the microporous membrane; and improving the bonding performance between the microporous membrane and perfluorosulfonic acid resin.
[0021] In some embodiments of the present invention, the nano-oxide particles are prepared by a sol-gel method; the conditions for the mixed reaction of the precursor solution of the platinum group metal and the nano-oxide powder are: temperature of 70-90°C, pH of 6.5-7.5, and reaction time of 0.5-1.5h; the calcination temperature is 150-250°C, and the calcination time is 0.5-1.5h.
[0022] In some embodiments of the present invention, the aging method is: allowing the uniformly mixed polytetrafluoroethylene resin powder and the nano-oxide particle material loaded with platinum group metals to stand at 25-40° C. for 24-72 hours.
[0023] In some embodiments of the present invention, the lubricant is one or more of petroleum ether, white oil, silicone oil, alcohols, and aromatic hydrocarbons; the amount of the lubricant added is 15-30% of the mass of the polytetrafluoroethylene resin powder; the extrusion pressure is 3-10MPa; the temperature of the longitudinal stretching is 300-350°C, and the stretching ratio of the longitudinal stretching is 600-1000%; the temperature of the transverse stretching is 200-220°C, and the stretching ratio of the transverse stretching is 1000-2500%; the temperature of the sintering and shaping is 350-400°C.
[0024] To achieve the above object, an embodiment of the third aspect of the present invention provides a proton exchange membrane comprising the microporous membrane as described above.
[0025] The beneficial effects of the proton exchange membrane of the embodiment of the present invention and the microporous membrane of the embodiment of the present invention are basically the same, and will not be described in detail here.
[0026] To achieve the above object, an embodiment of the fourth aspect of the present invention provides a method for preparing a proton exchange membrane, comprising adding a surfactant to a perfluorosulfonic acid resin solution to obtain a sulfonic acid resin solution;
[0027] Expanding the microporous membrane and soaking it in the sulfonic acid resin solution to form an impregnated membrane;
[0028] The impregnated membrane is dried to obtain the proton exchange membrane.
[0029] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:
[0031] Figure 1 FIG. 1 is a schematic diagram of a simple structure of a microporous membrane according to an embodiment of the present invention.
[0032] Figure 2 The schematic diagram is a state diagram of doping and mixing polytetrafluoroethylene resin particles and nano-oxide particles loaded with platinum group metals in a microporous membrane preparation process according to an embodiment of the present invention.
[0033] Figure 3 FIG. 4 is a schematic diagram of a simple structure of a proton exchange membrane according to an embodiment of the present invention.
[0034] Reference numerals:
[0035] 1-polytetrafluoroethylene fiber membrane body; 101-polytetrafluoroethylene fiber; 102-polytetrafluoroethylene fiber node; 2-nano oxide particles loaded with platinum group metals; 3-polytetrafluoroethylene resin particles; 100-microporous membrane; 200-perfluorosulfonic acid resin layer. DETAILED DESCRIPTION
[0036] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0037] The microporous membrane, the method for preparing the microporous membrane and the proton exchange membrane according to the embodiments of the present invention are described below with reference to the accompanying drawings.
[0038] Figure 1 FIG. 1 is a schematic diagram of a simple structure of a microporous membrane according to an embodiment of the present invention.
[0039] like Figure 1 As shown, the microporous membrane of the embodiment of the present invention comprises a polytetrafluoroethylene fiber membrane body 1 and nano-oxide particles 2 loaded with platinum group metals; the nano-oxide particles 2 loaded with platinum group metals are uniformly distributed in the pores of the polytetrafluoroethylene fiber membrane body 1.
[0040] The polytetrafluoroethylene fiber in the embodiment of the present invention is expanded polytetrafluoroethylene (ePTFE), and its structure is known, including polytetrafluoroethylene fiber membrane fiber and polytetrafluoroethylene fiber node (such as Figure 1 ), which is not the focus of the present invention.
[0041] The microporous membrane of the embodiment of the present invention, the nano-oxide loaded with platinum group metals is a hard chemically inert material, has the advantages of small particle size, large specific surface area, good hydrophilicity, strong surface adsorption, high surface energy, good mechanical properties, high wear resistance, dimensional stability, etc., is a good carrier reinforcement material, and it is compounded with a polytetrafluoroethylene fiber membrane to improve the wetting performance and self-humidifying performance of the microporous membrane; at the same time, the platinum group metal loaded with the nano-oxide of the platinum group metal is a good free radical quencher, which can quench free radicals in the use of the composite proton exchange membrane, is beneficial to the attachment of perfluorosulfonic acid resin and resistance to electrochemical degradation, reduces the hydrogen permeability of the proton exchange membrane, and improves the life of the entire proton exchange membrane.
[0042] Optionally, the diameter of the polytetrafluoroethylene fiber is 50-500 nm, and the average pore size is 100-400 nm; the particle size of the nano-oxide particles loaded with platinum group metals is below 100 nm.
[0043] Optionally, the nano-oxide particles loaded with platinum group metals are hydrophilic particles, wherein the platinum group metal is preferably platinum; the nano-oxide is one or more of nano-silicon dioxide, nano-titanium dioxide, and nano-zirconium dioxide, preferably nano-silicon dioxide. Nano-oxide loaded with platinum group metals is a hard, chemically inert material with the advantages of small particle size, large specific surface area, good hydrophilicity, strong surface adsorption, high surface energy, good mechanical properties, high wear resistance, and dimensional stability. It is a good carrier reinforcement material. Among them, the density of nano-silicon dioxide is 2.2g / cm 3 About the same as the density of polytetrafluoroethylene resin (2.1-2.3g / cm 3 ) is similar, and it is easier to mix evenly. It is a good reinforcement material for polytetrafluoroethylene membranes. It can play a certain reinforcing role in expanded polytetrafluoroethylene membrane materials, and at the same time can improve the wetting and self-wetting properties of ePTFE. The addition of nano-platinum group metals can reduce the hydrogen permeability of proton exchange membranes containing microporous membranes.
[0044] Nano-oxides can be prepared by oneself or purchased as commercial reagents on platforms such as Maclean and Sinopharm Reagent Network.
[0045] When nano-oxides are prepared by themselves, the sol-gel method can be used, wherein:
[0046] The preparation method of nano silicon dioxide is as follows: tetrabutyl silicate, ethanol and deionized water are hydrolyzed under alkaline conditions, and then stirred, centrifuged, freeze-dried and calcined to obtain nano silicon dioxide. The hydrolysis reaction equation is:
[0047] SiO4(C4H8)4+NH3H2O-SiO2+4C4H8OH+H2O;
[0048] In the preparation process of nano-silica: the volume ratio of tetrabutyl silicate, ethanol and deionized water is 1:1.5:2; the conditions of the hydrolysis reaction are: temperature 50°C, pH 5-6, reaction time 30min; freeze-drying temperature is -50°C, freeze-drying time is 24h, calcination temperature is 600°C, and calcination time is 1h.
[0049] The preparation method of nano titanium dioxide is as follows: tetrabutyl titanate and ethanol are configured into a clear first solution in a volume ratio of 1:3.5, and stirred at 50°C for 10 minutes; a mixed second solution of acetic acid, distilled water and ethanol in a volume ratio of 1:5:16 is prepared, and a small amount of hydrochloric acid is added to adjust the pH to 3. The first solution and the second solution are stirred and mixed in a volume ratio of 1:1, heated in a water bath at 40°C for 1 hour, centrifuged, washed three times with distilled water, freeze-dried at -50°C for 24 hours, and calcined at 600°C for 1 hour to obtain nano titanium dioxide.
[0050] The preparation method of nano zirconium dioxide can be carried out by referring to the preparation method of nano silicon dioxide and the preparation method of nano titanium dioxide.
[0051] Optionally, the loading amount of platinum group metal in the nano-oxide particles loaded with platinum group metal is 1-50wt%; and the mass ratio of the polytetrafluoroethylene fiber membrane body to the nano-oxide particles loaded with platinum group metal is 100:1-20.
[0052] The method for preparing the microporous membrane of the embodiment of the present invention comprises the following steps:
[0053] A: The precursor solution of the platinum group metal is mixed with the nano-oxide powder, and a certain amount of ammonia water is added. The mixture is reacted under stirring conditions, and then centrifuged and calcined to obtain nano-oxide particles loaded with platinum group metals. The conditions for the mixed reaction of the precursor solution of the platinum group metal and the nano-oxide powder are: temperature of 70-90°C, pH of 6.5-7.5, reaction time of 0.5-1.5h; calcination temperature of 150-250°C, calcination time of 0.5-1.5h.
[0054] B: Select polytetrafluoroethylene resin powder with a particle size of about 3μm-5μm, and the polytetrafluoroethylene resin crystallinity is required to be not less than 98% to ensure the strength and stretchability of the ePTFE microporous membrane.
[0055] C: Taking 100 parts of the added mass of polytetrafluoroethylene resin, weigh 1-20 parts by mass of nano-oxide particles loaded with platinum group metals, place the polytetrafluoroethylene resin and the nano-oxide particles loaded with platinum group metals in a mixer and mix them for 12 hours (the doping and mixing state is as follows Figure 2 shown).
[0056] D: Ripening treatment: The uniformly mixed raw materials are placed at 25-40°C for aging for not less than 24 hours (preferably 24-72 hours).
[0057] E: Add 15-30 parts by weight of lubricant to the matured mixture, mix thoroughly and set aside (lubricants mainly include mixed organic solvents such as petroleum ether, white oil, silicone oil, alcohols, aromatic hydrocarbons, etc.).
[0058] F: The mixed material with the lubricant added is extruded at a pressure of 3-10 MPa to form a raw material blank.
[0059] G: The blank raw material is rolled at a temperature of 50-80° C. to form a first rolled film, the thickness of which is about 1 mm.
[0060] H: Drying treatment: The first calendered film is heated and dried at 200-300°C to remove the lubricant in the first calendered film to obtain a second calendered film. The lubricant can be recycled.
[0061] I: Longitudinal stretching: Under the temperature condition of 300-350° C., the second calendered film is longitudinally stretched by 600-1000%.
[0062] J: Transverse stretching: Under the temperature condition of 200-220°C, the second calendered film which has been longitudinally stretched by pressing is transversely stretched by 1000-2500%.
[0063] K: Under the temperature condition of 350-400° C., the PTFE membrane (i.e., the second calendered membrane) that has been longitudinally stretched and transversely stretched is sintered and shaped to finally form the microporous membrane (e.g., Figure 1 The sintering temperature is increased in a gradient manner to ensure uniform pore size and fixed strength.
[0064] The microporous membrane prepared by the above preparation method will produce the following effects:
[0065] 1. Nano-oxide particles loaded with platinum group metals can be evenly distributed in the pores of the ePTFE microporous membrane.
[0066] 2. The nano-oxide particles loaded with platinum group metals have a large specific surface area and can provide a certain degree of hydrophilicity for ePTFE.
[0067] 3. The platinum group metals on the surface of the nano-oxide particles loaded with platinum group metals are good free radical quenchers, which can quench free radicals during the use of the composite proton exchange membrane, and are beneficial to the adhesion of perfluorosulfonic acid resin and resistance to electrochemical degradation.
[0068] 4. Nano-oxide particles loaded with platinum group metals have a large specific surface area and adsorption effect, which can interact with PTFE fibers and provide a certain degree of enhancement. Figure 3 As shown, the proton exchange membrane according to the embodiment of the present invention includes the microporous membrane 100 according to the embodiment of the present invention.
[0069] Preferably, the proton exchange membrane further comprises a perfluorosulfonic acid resin layer 200, and the perfluorosulfonic acid resin layer is wrapped on the outer surface of the microporous membrane.
[0070] More preferably, the perfluorosulfonic acid resin layer in the proton exchange membrane is disposed on two opposite sides of the microporous membrane (eg Figure 3 As shown), and the perfluorosulfonic acid resin layer preferably covers the entire side of the microporous membrane where it is located.
[0071] The method for preparing a proton exchange membrane according to an embodiment of the present invention comprises the following steps:
[0072] (1) adding a surfactant to a perfluorosulfonic acid resin solution to obtain a sulfonic acid resin solution;
[0073] (2) expanding the microporous membrane and immersing it in a sulfonic acid resin solution to form an impregnated membrane;
[0074] (3) Drying the impregnated membrane to obtain a proton exchange membrane.
[0075] Optionally, in step (1), the solid content of the perfluorosulfonic acid resin solution is 10-30wt%, preferably 20wt%; the amount of the surface additive added is 0.5-1.5% of the mass of the perfluorosulfonic acid resin solution, preferably 1%; the surfactant can be selected from Triton X100, Triton X114, etc.
[0076] Optionally, in step (2), the immersion time of the microporous membrane in the sulfonic acid resin solution is 3-8 min, preferably 5 min.
[0077] Optionally, in step (3), the drying temperature is 80-100° C., and the drying time is 10 min.
[0078] The microporous membrane and its preparation method, the proton exchange membrane and its preparation method of the present invention are described below with reference to specific embodiments and comparative examples.
[0079] Unless otherwise specified, the raw materials, reagents and equipment involved in the embodiments of the present invention are all commercially available; the methods involved in the embodiments of the present invention are all conventional methods unless otherwise specified.
[0080] 1. Examples and Comparative Examples
[0081] Example 1
[0082] (1) Preparation of microporous membrane
[0083] A: Preparation of nano-silica: Tetrabutyl silicate, ethanol and deionized water were prepared into a clear solution in a volume ratio of 1:1.5:2, stirred (magnetic stirring) at 50°C for 30 minutes, and ammonia solution was added dropwise while stirring until the pH was 5-6, followed by centrifugation. The silica gel obtained by centrifugation was freeze-dried at -50°C for 24 hours and calcined at 600°C for 1 hour to obtain nano-silica.
[0084] B: Chloroplatinic acid: nano-silica: deionized water were mixed in a mass ratio of 1:10:500, and ammonia water was added dropwise to a pH of 7 at 80°C with stirring (magnetic stirring). The mixture was stirred for 1 hour and then centrifuged. The Pt-loaded particles obtained by centrifugation were then washed three times with deionized water and calcined at 200°C under nitrogen for 1 hour to obtain Pt-loaded nano-silica particles, in which the Pt loading was 3%.
[0085] C: Select polytetrafluoroethylene resin powder with a particle size of about 3-5 μm and a crystallinity of 98.5%.
[0086] D: Taking the added mass of polytetrafluoroethylene resin as 100 parts, weigh 7 parts of the mass of Pt-loaded nano-silica particles, place the polytetrafluoroethylene and Pt-loaded nano-silica particles in a mixer and mix them for 12 hours.
[0087] E: Aging treatment: The mixed raw materials are placed at 30°C for 36 hours.
[0088] F: Add 20 parts by mass of lubricant petroleum ether to the matured mixture, mix thoroughly and set aside.
[0089] G: The mixed material with lubricant added is extruded into a raw material blank at a pressure of 5 MPa.
[0090] H: The blank raw material is rolled at 65° C. to form a first rolled film, the thickness of which is 1 mm.
[0091] I: Drying treatment: The first calendered film is heated and dried at 250° C. to remove the lubricant in the first calendered film, thereby obtaining a second calendered film, and the lubricant is recycled.
[0092] J: Longitudinal stretching: The second calendered film was longitudinally stretched by 1000% at 300°C.
[0093] K: Transverse stretching: Under the temperature condition of 200° C., the second calendered film which has been longitudinally stretched by pressing is subjected to 2000% transverse stretching.
[0094] L: The PTFE membrane that has been longitudinally stretched and transversely stretched (ie, the second calendered membrane) is shaped at 350° C. for 15 minutes to obtain the ePTFE microporous membrane of this example.
[0095] (2) Preparation of proton exchange membrane
[0096] 1 g of surfactant Triton X100 was added to 100 mL of a perfluorosulfonic acid resin solution with a solid content of 20 wt% to obtain a sulfonic acid resin solution; the ePTFE microporous membrane prepared in this embodiment was expanded and immersed in the sulfonic acid resin solution for 5 min, so that the upper and lower surfaces of the ePTFE microporous membrane were impregnated with the sulfonic acid resin solution to form an impregnated membrane; the impregnated membrane was dried at 90° C. for 10 min to obtain the proton exchange membrane of this embodiment.
[0097] Example 2
[0098] (1) Preparation of microporous membrane
[0099] A: Preparation of nano-silica: Tetrabutyl silicate, ethanol and deionized water were prepared into a clear solution in a volume ratio of 1:1.5:2, stirred (magnetic stirring) at 50°C for 30 minutes, and ammonia solution was added dropwise while stirring until the pH was 5-6, followed by centrifugation. The silica gel obtained by centrifugation was freeze-dried at -50°C for 24 hours and calcined at 600°C for 1 hour to obtain nano-silica.
[0100] B: Chloroplatinic acid: nano-silica: deionized water were mixed in a mass ratio of 1:10:500, and ammonia water was added dropwise to a pH of 7 at 80°C with stirring (magnetic stirring). The mixture was stirred for 1 hour and then centrifuged. The Pt-loaded particles obtained by centrifugation were then washed three times with deionized water and calcined at 200°C under nitrogen for 1 hour to obtain Pt-loaded nano-silica particles, in which the Pt loading was 3%.
[0101] C: Select polytetrafluoroethylene resin powder with a particle size of about 3-5μm.
[0102] D: Taking the added mass of polytetrafluoroethylene resin as 100 parts, weigh 5 parts of the mass of Pt-loaded nano-silica particles, place the polytetrafluoroethylene and Pt-loaded nano-silica particles in a mixer and mix them for 12 hours.
[0103] E: Aging treatment: The mixed raw materials are placed at 25°C for 48 hours.
[0104] F: Add 20 parts by weight of lubricant polydimethylsiloxane to the matured mixture, mix thoroughly and set aside.
[0105] G: The mixed material with lubricant added is extruded into a raw material blank at a pressure of 5 MPa.
[0106] H: The blank raw material is rolled at 50° C. to form a first rolled film, and the thickness of the first rolled film is 1.2 mm.
[0107] I: Drying treatment: The first calendered film is heated and dried at 250° C. to remove the lubricant in the first calendered film, thereby obtaining a second calendered film, and the lubricant is recycled.
[0108] J: Longitudinal stretching: The second calendered film was longitudinally stretched by 800% at 350°C.
[0109] K: Transverse stretching: Under the temperature condition of 200° C., the second calendered film which has been longitudinally stretched by pressing is subjected to 1200% transverse stretching.
[0110] L: The PTFE membrane that has been longitudinally stretched and transversely stretched (ie, the second calendered membrane) is shaped at 380° C. for 15 minutes to obtain the ePTFE microporous membrane of this embodiment.
[0111] (2) Preparation of proton exchange membrane
[0112] 1 g of surfactant Triton X100 was added to 100 mL of a perfluorosulfonic acid resin solution with a solid content of 15 wt% to obtain a sulfonic acid resin solution; the ePTFE microporous membrane prepared in this embodiment was expanded and immersed in the sulfonic acid resin solution for 3 minutes, so that the upper and lower surfaces of the ePTFE microporous membrane were impregnated with the sulfonic acid resin solution to form an impregnated membrane; the impregnated membrane was dried at 80° C. for 10 minutes to obtain the proton exchange membrane of this embodiment.
[0113] Example 3
[0114] (1) Preparation of microporous membrane
[0115] A: Preparation of nano-silica: Tetrabutyl silicate, ethanol and deionized water were prepared into a clear solution in a volume ratio of 1:1.5:2, stirred (magnetic stirring) at 50°C for 30 minutes, and ammonia solution was added dropwise while stirring until the pH was 5-6, followed by centrifugation. The silica gel obtained by centrifugation was freeze-dried at -50°C for 24 hours and calcined at 600°C for 1 hour to obtain nano-silica.
[0116] B: Chloroplatinic acid: nano-silica: deionized water were mixed in a mass ratio of 1:3:500, and ammonia water was added dropwise to a pH of 7 at 80°C with stirring (magnetic stirring). The stirring was continued for 1 hour and then centrifuged. The Pt-loaded particles obtained by centrifugation were then washed three times with deionized water and calcined at 200°C under nitrogen for 1 hour to obtain Pt-loaded nano-silica particles, in which the Pt loading was 11%.
[0117] C: Select polytetrafluoroethylene resin powder with a particle size of about 3-5μm.
[0118] D: Taking the added mass of polytetrafluoroethylene resin as 100 parts, weigh 7 parts of the mass of Pt-loaded nano-silica particles, place the polytetrafluoroethylene and Pt-loaded nano-silica particles in a mixer and mix them for 12 hours.
[0119] E: Aging treatment: The mixed raw materials are placed at 30°C for 30 hours.
[0120] F: Add 20 parts by mass of lubricant n-heptanol to the matured mixture, mix thoroughly and set aside.
[0121] G: The mixed material with lubricant added is extruded into a raw material blank at a pressure of 5 MPa.
[0122] H: The blank raw material is rolled at 80° C. to form a first rolled film, and the thickness of the first rolled film is 0.9 mm.
[0123] I: Drying treatment: The first calendered film is heated and dried at 250° C. to remove the lubricant in the first calendered film, thereby obtaining a second calendered film, and the lubricant is recycled.
[0124] J: Longitudinal stretching: The second calendered film was longitudinally stretched by 1000% at 330°C.
[0125] K: Transverse stretching: Under the temperature condition of 210° C., the second calendered film which has been longitudinally stretched by pressing is subjected to 2000% transverse stretching.
[0126] L: The PTFE membrane that has been longitudinally stretched and transversely stretched (ie, the second calendered membrane) is shaped at 350° C. for 15 minutes to obtain the ePTFE microporous membrane of this example.
[0127] (2) Preparation of proton exchange membrane
[0128] 1 g of surfactant Triton X100 was added to 100 L of a perfluorosulfonic acid resin solution with a solid content of 20 wt% to obtain a sulfonic acid resin solution; the ePTFE microporous membrane prepared in this embodiment was expanded and immersed in the sulfonic acid resin solution for 5 min, so that the upper and lower surfaces of the ePTFE microporous membrane were impregnated with the sulfonic acid resin solution to form an impregnated membrane; the impregnated membrane was dried at 90° C. for 10 min to obtain the proton exchange membrane of this embodiment.
[0129] Example 4
[0130] (1) Preparation of microporous membrane
[0131] A: Preparation of nano-silica: Tetrabutyl silicate, ethanol and deionized water were prepared into a clear solution in a volume ratio of 1:1.5:2, stirred (magnetic stirring) at 50°C for 30 minutes, and ammonia solution was added dropwise while stirring until the pH was 5-6, followed by centrifugation. The silica gel obtained by centrifugation was freeze-dried at -50°C for 24 hours and calcined at 600°C for 1 hour to obtain nano-silica.
[0132] B: Chloroplatinic acid: nano-silica: deionized water were mixed in a mass ratio of 1:1:500, and ammonia water was added dropwise to a pH of 7 at 80°C with stirring (magnetic stirring). The stirring was continued for 1 hour and then centrifuged. The Pt-loaded particles obtained by centrifugation were then washed three times with deionized water and calcined at 200°C under nitrogen for 1 hour to obtain Pt-loaded nano-silica particles, in which the Pt loading was 27%.
[0133] C: Select polytetrafluoroethylene resin powder with a particle size of about 3-5μm.
[0134] D: Taking the added mass of polytetrafluoroethylene resin as 100 parts, weigh 1 part of the mass of Pt-loaded nano-silica particles, place the polytetrafluoroethylene and Pt-loaded nano-silica particles in a mixer and mix them for 12 hours.
[0135] E: Aging treatment: The mixed raw materials are placed at 30°C for 80 hours.
[0136] F: Add 20 parts by mass of lubricant (10 parts by mass of petroleum ether and 10 parts by mass of polydimethylsiloxane) to the matured mixture, mix thoroughly and set aside.
[0137] G: The mixed material with lubricant added is extruded into a raw material blank at a pressure of 5 MPa.
[0138] H: The blank raw material is rolled at 65° C. to form a first rolled film, the thickness of which is 1 mm.
[0139] I: Drying treatment: The first calendered film is heated and dried at 250° C. to remove the lubricant in the first calendered film, thereby obtaining a second calendered film, and the lubricant is recycled.
[0140] J: Longitudinal stretching: The second calendered film was longitudinally stretched by 1000% at 340°C.
[0141] K: Transverse stretching: Under the temperature condition of 210° C., the second calendered film which has been longitudinally stretched by pressing is subjected to 2000% transverse stretching.
[0142] L: The PTFE membrane that has been longitudinally stretched and transversely stretched (ie, the second calendered membrane) is shaped at 350° C. for 15 minutes to obtain the ePTFE microporous membrane of this example.
[0143] (2) Preparation of proton exchange membrane
[0144] 1 g of surfactant Triton X114 was added to 100 mL of a perfluorosulfonic acid resin solution with a solid content of 25 wt% to obtain a sulfonic acid resin solution; the ePTFE microporous membrane prepared in this embodiment was expanded and immersed in the sulfonic acid resin solution for 8 minutes so that the upper and lower surfaces of the ePTFE microporous membrane were both impregnated with the sulfonic acid resin solution to form an impregnated membrane; the impregnated membrane was dried at 100° C. for 10 minutes to obtain the proton exchange membrane of this embodiment.
[0145] Example 5
[0146] (1) Preparation of microporous membrane
[0147] A: Preparation of nano titanium dioxide: Tetrabutyl titanate and ethanol were prepared into a clear first solution in a volume ratio of 1:3.5, and stirred at 50°C for 10 minutes; a second mixed solution of acetic acid, distilled water and ethanol in a volume ratio of 1:5:16 was prepared, and a small amount of hydrochloric acid was added to adjust the pH to 3. The first solution and the second solution were stirred and mixed in a volume ratio of 1:1, heated in a water bath at 40°C for 1 hour, and centrifuged. The titanium dioxide gel obtained by centrifugation was washed three times with distilled water, freeze-dried at -50°C for 24 hours, and calcined at 600°C for 1 hour to obtain nano titanium dioxide.
[0148] B: Chloroplatinic acid: nano-titanium dioxide: deionized water are mixed in a mass ratio of 1:5:500, and ammonia water is added dropwise to a pH of 7 at 80°C with stirring (magnetic stirring). Stirring is continued for 1 hour and then centrifuged. The Pt-loaded particles obtained by centrifugation are then washed three times with deionized water and calcined at 200°C under nitrogen for 1 hour to obtain Pt-loaded nano-silica particles, in which the Pt loading amount is 6%.
[0149] C: Select polytetrafluoroethylene resin powder with a particle size of about 3-5μm.
[0150] D: Taking the added mass of polytetrafluoroethylene resin as 100 parts, weigh 3 parts of the mass of Pt-loaded nano-titanium dioxide particles, place the polytetrafluoroethylene and Pt-loaded nano-titanium dioxide particles in a mixer and mix them for 12 hours.
[0151] E: Aging treatment: The mixed raw materials are placed at 30°C for 72 hours.
[0152] F: Add 20 parts by mass of lubricant petroleum ether to the matured mixture, mix thoroughly and set aside.
[0153] G: The mixed material with lubricant added is extruded into a raw material blank at a pressure of 5 MPa.
[0154] H: The blank raw material is rolled at 65° C. to form a first rolled film, the thickness of which is 1 mm.
[0155] I: Drying treatment: The first calendered film is heated and dried at 250° C. to remove the lubricant in the first calendered film, thereby obtaining a second calendered film, and the lubricant is recycled.
[0156] J: Longitudinal stretching: The second calendered film was longitudinally stretched by 1000% at 320°C.
[0157] K: Transverse stretching: Under the temperature condition of 220° C., the second calendered film which has been longitudinally stretched by pressing is subjected to 2000% transverse stretching.
[0158] L: The PTFE membrane that has been longitudinally stretched and transversely stretched (ie, the second calendered membrane) is shaped at 350° C. for 15 minutes to obtain the ePTFE microporous membrane of this example.
[0159] (2) Preparation of proton exchange membrane
[0160] 1 g of surfactant Triton X114 was added to 100 mL of a perfluorosulfonic acid resin solution with a solid content of 20 wt% to obtain a sulfonic acid resin solution; the ePTFE microporous membrane prepared in this embodiment was expanded and immersed in the sulfonic acid resin solution for 5 minutes so that the upper and lower surfaces of the ePTFE microporous membrane were impregnated with the sulfonic acid resin solution to form an impregnated membrane; the impregnated membrane was dried at 90° C. for 10 minutes to obtain the proton exchange membrane of this embodiment.
[0161] Example 6
[0162] This embodiment is basically the same as Embodiment 1, except that during the preparation of the microporous membrane, the stretching ratio of the longitudinal stretching is 600%, and the stretching ratio of the transverse stretching is 1750%.
[0163] Example 7
[0164] This embodiment is basically the same as Embodiment 1, except that during the preparation of the microporous membrane, the stretching ratio of the longitudinal stretching is 900%, and the stretching ratio of the transverse stretching is 2500%.
[0165] Example 8
[0166] This embodiment is basically the same as the embodiment 1, except that: during the preparation of the microporous membrane, the platinum group metal in the nano-oxide particles loaded with platinum group metals is palladium, and the chloroplatinic acid in step B is replaced by chloropalladic acid.
[0167] Example 9
[0168] This embodiment is basically the same as the embodiment 1, except that: during the preparation of the microporous membrane, 10 parts by weight of the added polytetrafluoroethylene resin is used as 100 parts, and 10 parts by weight of the Pt-loaded nano-silica particles are weighed.
[0169] Example 10
[0170] This embodiment is basically the same as the embodiment 1, except that: during the preparation of the microporous membrane, the mass of the added polytetrafluoroethylene resin is 100 parts, and the mass of the Pt-loaded nano-silica particles is weighed to 19 parts.
[0171] Embodiment 11
[0172] This embodiment is basically the same as the embodiment 1, except that: during the preparation of the microporous membrane, chloroplatinic acid: nano-silica: deionized water are mixed in a mass ratio of 5:2:500; and the Pt-loaded nano-silica particles have a Pt loading of 48%.
[0173] Comparative Example
[0174] The microporous membrane of this comparative example is ePTFE sold in a certain market, and the proton exchange membrane is a proton exchange membrane prepared by using the ePTFE sold in the market. The preparation method of the proton exchange membrane is the same as that of Example 1.
[0175] 2. Performance Testing
[0176] The thickness, tensile strength, elongation at break, water contact angle, porosity and pore size of the microporous membranes of Examples 1-7 and the comparative example were tested. The test results are shown in Table 1.
[0177] The fluoride ion loss rate of the proton exchange membranes of Examples 1-7 and the comparative example was tested, and the test results are shown in Table 1. The test method for the fluoride ion loss rate is as follows: a 5cm*5cm proton exchange membrane is weighed and immersed in 1500mL Fenton reagent (15% H2O2; 20ppm Fe 3+ ) for 24 hours, and then the proton exchange membrane was removed and the Fenton reagent was tested. - Ion concentration, measured F - Ion content, compared with the mass of the proton exchange membrane, gives F - Ion loss rate. - Ion concentration and content characterize the electrochemical degradation of the proton exchange membrane caused by the attack of free radicals in the Fenton reagent. - The higher the ion content, the - The higher the ion loss rate, the worse the proton exchange membrane's anti-degradation performance.
[0178] Table 1 Performance test results of microporous membrane and proton exchange membrane of Examples 1-7 and Comparative Examples
[0179]
[0180]
[0181] It can be seen from Table 1 that the tensile strength and elongation at break of the microporous membrane of the embodiment of the present invention are improved compared with the microporous membrane of the comparative example, and the hydrophilic property is improved; the fluoride ion loss rate of the proton exchange membrane of the embodiment of the present invention is only 31.8%-54.5% of that of the comparative example, which shows that the anti-degradation performance of the proton exchange membrane of the embodiment of the present invention is greatly improved.
[0182] In summary, the microporous membrane of the embodiment of the present invention can improve the wetting performance and self-humidification performance of the microporous membrane by adding nano-oxides loaded with platinum group metals such as Pt to quench free radicals. At the same time, the microporous membrane has excellent mechanical properties, good membrane material surface properties, and high porosity. It can be widely used in the field of fuel cell proton exchange membrane materials, reduce the hydrogen permeability of ePTFE composite reinforced proton exchange membranes, improve resistance to electrochemical degradation, thereby increasing the life of the proton exchange membrane and improving the overall application performance of the proton exchange membrane.
[0183] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0184] In the present invention, the terms "first", "second", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features.
[0185] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A microporous membrane, characterized in that: It is composed of a polytetrafluoroethylene fiber membrane body and nano-oxide particles loaded with platinum group metals; The nano-oxide particles loaded with platinum group metals are uniformly distributed in the pores of the polytetrafluoroethylene fiber membrane body; The particle size of the nano-oxide particles loaded with platinum group metals is less than 100 nm; The mass ratio of the polytetrafluoroethylene fiber membrane body to the nano-oxide particles loaded with platinum group metals is 100:1-20; The nano-oxide particles loaded with platinum group metals are hydrophilic particles; the nano-oxide is one or more of nano-silicon dioxide, nano-titanium dioxide and nano-zirconium dioxide.
2. The microporous membrane according to claim 1, characterized in that The diameter of the polytetrafluoroethylene fiber is 50-500 nm, and the average pore size is 100-400 nm.
3. The microporous membrane according to claim 1, characterized in that The loading amount of the platinum group metal in the nano-oxide particles loaded with platinum group metal is 1-50wt%.
4. A method for preparing a microporous membrane according to any one of claims 1 to 3, characterized in that: include The precursor solution of the platinum group metal is mixed with the nano-oxide powder for reaction, and then centrifugally separated and calcined to obtain the nano-oxide particles loaded with the platinum group metal; The polytetrafluoroethylene resin powder and the nano-oxide particles loaded with platinum group metals are mixed and matured, and extruded under the action of a lubricant to form a raw material blank; The raw material blank is rolled to form a first rolled film, and the first rolled film is dried to obtain a second rolled film; The microporous membrane can be obtained by sequentially stretching the second calendered membrane longitudinally and transversely and then sintering and shaping.
5. The method for preparing a microporous membrane according to claim 4, characterized in that: The nano-oxide particles are prepared by a sol-gel method; the conditions for the mixed reaction of the precursor solution of the platinum group metal and the nano-oxide powder are: temperature of 70-90°C, pH of 6.5-7.5, and reaction time of 0.5-1.5h; the calcination temperature is 150-250°C, and the calcination time is 0.5-1.5h.
6. The method for preparing a microporous membrane according to claim 4, characterized in that: The aging method is: the uniformly mixed polytetrafluoroethylene resin powder and the nano-oxide particle material loaded with platinum group metals are placed at 25-40° C. for 24-72 hours.
7. The method for preparing a microporous membrane according to claim 4, characterized in that: The lubricant is one or more of petroleum ether, white oil, silicone oil, alcohols, and aromatic hydrocarbons; the amount of the lubricant added is 15-30% of the mass of the polytetrafluoroethylene resin powder; the extrusion pressure is 3-10 MPa; the longitudinal stretching temperature is 300-350°C, and the longitudinal stretching ratio is 600-1000%; the transverse stretching temperature is 200-220°C, and the transverse stretching ratio is 1000-2500%; the sintering temperature is 350-400°C.
8. A proton exchange membrane, characterized in that: The invention comprises the microporous membrane as claimed in any one of claims 1 to 3.
9. A method for preparing a proton exchange membrane as claimed in claim 8, characterized in that: include Adding a surfactant into the perfluorosulfonic acid resin solution to obtain a sulfonic acid resin solution; Expanding the microporous membrane and soaking it in the sulfonic acid resin solution to form an impregnated membrane; The impregnated membrane is dried to obtain the proton exchange membrane.
